Ankle dorsiflexion range of motion and trunk muscle endurance are not associated with hip and knee kinematics during the forward step-down test in CrossFit® practitioners - de Souza, T. V.; Rabello, R.; da Rocha, E. S.; Rodrigues, R. (Sport Sciences for Health, 2023)
Purpose CrossFit® (CF) is a high-intensity training method with a large number of practitioners, having an injury prevalence similar to other sports. Although excessive dynamic knee valgus is related to several injuries and associated with the trunk muscles` endurance and dorsiflexion range of motion (DF-ROM), no study has evaluated these parameters in CF practitioners. The aim of the study was to investigate the association between lower limb alignment during the step-down test, DF-ROM and lateral trunk muscle endurance in CrossFit® (CF) practitioners.